Pengembangan E-Modul Matematika Berbasis Numbered Head Together (NHT) pada Materi SPLDV - Yola Putri Anggraini; Nisah Ayu Siregar (YASIN, 2026)
Mathematics learning, particularly on the topic of Systems of Linear Equations in Two Variables (SPLDV), still faces challenges in improving students’ understanding, so learning innovations are needed that are capable of integrating technology with collaborative activities. This study aims to evaluate the effectiveness of an e-module based on the Numbered Head Together (NHT) cooperative learning model in improving students’ understanding of SPLDV material. This study used a quantitative approach with a quasi-experimental design, involving 60 students from two junior secondary school classes selected through purposive sampling. Data were collected through pre-test and post-test instruments as well as questionnaires to assess students’ responses, and were then analyzed using descriptive statistics and the t-test. The results showed that the experimental group using the NHT-based e-module experienced a 32% increase in post-test scores, higher than the control group, which experienced a 15% increase. These findings contribute to the development of technology-based cooperative learning and expand understanding of the implementation of e-modules in mathematics learning. The conclusion of this study emphasizes the importance of collaboration among students in improving mathematical understanding, and shows that the use of an NHT-based e-module can serve as a strategic alternative in learning SPLDV. The implications of this study include a theoretical contribution to the literature on technology-based learning and practical implications for curriculum development and teacher training.